DYNAMICS OF EXPERIENCE AND EXPRESSION IN RELIGIOUS WORSHIP - Vineeth, V. F. (Journal of Dharma, 2006)
Jayadev was a young man brought up in a good family. Though his parents were religious minded, they did not instruct him on the need of religious worship. Jayadev loved nature and one day he went out for a walk into the forest. He climbed the nearby hill and had a panoramic view of the land from above. It looked very beautiful: lakes and lagoons, mountains and clouds, trees and rocks, a lovely pathway running along the tree lines and two small cottages in the valley. The whole scene was marvelous and attractive. “Really this is a place of God,” he said to himself. Where many commercially minded people find an apt tourist spot, Jayadev saw a dwelling place of God, His spirit hovering over the mountains and valleys like a lovely bird fluttering its wings, flying high up and also stooping down, watching all that has been made. Jayadev slowly raised his head along with the fluttering wings of the bird, raised his eyes into the skies and beyond the clouds. What is there! There is nothing, mere emptiness or empty space! “Really there is nothing?” he asked himself. There is something, he felt; there is a touching presence, some unknown presence which invited him inevitably, bewitchingly and invisibly. Without his knowledge his hands were raised and for a moment he remained in silence. He did not know that he was worshipping the One whose enrapturing presence he felt in his heart than in his head.